Does human foot anthropometry relate to plantar flexor fascicle mechanics and metabolic energy cost across various walking speeds? - Papachatzis, N.; Ray, S. F.; Takahashi, K. Z. (Journal of Experimental Biology, 2023)
Foot structures define the leverage in which the ankle muscles push off against the ground during locomotion. While prior studies have indicated that inter-individual variation in anthropometry (e.g. heel and hallux lengths) can directly affect force production of ankle plantar flexor muscles, its effect on the metabolic energy cost of locomotion has been inconclusive. Here, we tested the hypotheses that shorter heels and longer halluces are associated with slower plantar flexor (soleus) shortening velocity and greater ankle plantar flexion moment, indicating enhanced force potential as a result of the force-velocity relationship. We also hypothesized that such anthropometry profiles would reduce the metabolic energy cost of walking at faster walking speeds. Healthy young adults (N=15) walked at three speeds (1.25, 1.75 and 2.00 m s-1), and we collected in vivo muscle mechanics (via ultrasound), activation (via electromyography) and whole-body metabolic energy cost of transport (via indirect calorimetry). Contrary to our hypotheses, shorter heels and longer halluces were not associated with slower soleus shortening velocity or greater plantar flexion moment. Additionally, longer heels were associated with reduced metabolic cost of transport, but only at the fastest speed (2.00 m s-1, R2=0.305, P=0.033). We also found that individuals with longer heels required less increase in plantar flexor (soleus and gastrocnemius) muscle activation to walk at faster speeds, potentially explaining the reduced metabolic cost.